Genetic engineering of low-temperature polyhydroxyalkanoate production by Acidovorax sp. A1169, a psychrophile isolated from a subglacial outflow - Grzesiak, Jakub; Gawor, Jan; Rogala, Małgorzata Marta; Kouřilová, Xenie; Obruča, Stanislav (Extremophiles, 2023)
In recent years, extremophilic microorganisms have been employed as producers of the microbial bioplastics polyhydroxyalkanoates (PHA), which are of great biotechnological value. Nevertheless, cold-loving or psychrophilic (cryophilic) bacteria have been neglected in this regard. Here, we present an investigation of the Arctic glacier-derived PHA producer Acidovorax sp. A1169. Biolog GEN III Microplates were used as a screening tool to identify the most suitable carbon substrate concerning PHA synthesis. The strain produced homopolymer poly(3-hydroxybutyrate) (PHB) most efficiently (2 g/L) at a temperature of 15 °C when supplied with fructose or mannitol as carbon sources with a substantial decrease of PHB biosynthesis at 17.5 °C. The PHB yield did not increase considerably or even decreased when carbon source concentration exceeded 10 g/L hinting that the strain is oligotrophic in nature. The strain was also capable of introducing 3-hydroxyvalerate (3HV) into the polymer structure, which is known to improve PHA thermoplastic properties. This is the first investigation providing insight into a PHA biosynthesis process by means of a true psychrophile, offering guidelines on polar-region bacteria cultivation, production of PHA and also on the methodology for genetic engineering of psychrophiles.
Keywords: genetické inženýrství; Temperature; Genetic Engineering; Comamonadaceae; Carbon; uhlík; polyhydroxyalkanoáty; teplota; Polyhydroxyalkanoates